CULTURE AND GENDER: AN IDEOLOGICAL GAP BETWEEN MALES AND FEMALES - Rocha- Sánchez, Tania E.; Díaz- Loving, Rolando (Anales de Psicología / Annals of Psychology, 2005)
The current definition of gender makes reference to a complex integration of behaviors, beliefs, attributes and social representations and prescriptions, used in a cultural group as a function of the value, construction and interpretation made of perceived anatomical differences. This differentiation covers a division of activities, identity formation and interactions between males and females. Research clearly points towards a basis of biological parameters, which are molded by a social construction process. Thus, each culture develops a series of norms and meanings that determine the manifestation of gender. In order to study the stereotypical and prototypical beliefs and values of Mexican subjects, an inventory measuring perceived and assigned gender ideology was applied to 400 adults. Results, related to sex, age and education, are discussed in relation to the effect that socio-cultural transformations have had on the permanence and transition of gender ideology within the culture and its possible causes and consequences.